(untitled) (Reflection and Critique Law Magazine, 2023)
Based on the premise that the auction is a bidding procedure whose disqualification of bidders should be an exceptional measure, since it implies the impossibility of the Public Administration contract the best proposal obtained in the bidding, the present study evaluates the decision-making pattern of the Court of Account of the City of São Paulo in relation to this theme. In this context, the article also investigates the theme of legal consequentialism and legal certainty, pointing out the decision-making pattern of the Court of Auditors on the subject.